Heat conduction across interface between two materials. Part II: weak conducting interface - Syed Tanvir Ashraf (Nanyang Technological University, 2025)
Heat is a form of energy transferred from one system to another due to temperature differences. Heat transfer occurs from a higher temperature system to a lower temperature system. The three primary modes of heat transfer are Conduction, Convection, and Radiation. Conduction requires two mediums in direct contact with each other, and energy is transferred from one particle of one medium to another. Convection is the movement of fluids between two regions due to the temperature difference. Thermal Radiation does not require any medium, heat energy from radiation is transmitted through electromagnetic waves.